The impacts of socio-economic indicator on urban growth in Selangor, Malaysia - Ibrahim, Illyani; Asmawi, M. Zainora; Abu Samah, Azizan; Salleh, Siti Aekbal (Institute of Physics Publishing, 2018)
All cities in the world including Malaysia are experiencing rapid urbanization which has given significant impact on the variability of socio-economy. The present study is conducted to investigate the expansion of urban growth in the state of Selangor by selecting appropriate socio-economic indicators used in urban growth studies. The study partly aims to describe a set of socio-indicators that most directly contribute to urban growth analysis. The objectives of the research are (i) to test the availability of dataset of each socio-economic indicators, (ii) examine the changes of each indicator in a decade, and (iii) propose new criteria for the selection of socio-economic indicators. Findings are derived from the secondary data from a local government agency and available digital datasets. The result advocates the use of criteria to validate the indicators to be used in future studies.